2010
DOI: 10.3390/s101009407
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Bragg Grating Sensor for Fault Detection in Radial and Network Transmission Lines

Abstract: In this paper, a fiber optic based sensor capable of fault detection in both radial and network overhead transmission power line systems is investigated. Bragg wavelength shift is used to measure the fault current and detect fault in power systems. Magnetic fields generated by currents in the overhead transmission lines cause a strain in magnetostrictive material which is then detected by Fiber Bragg Grating (FBG). The Fiber Bragg interrogator senses the reflected FBG signals, and the Bragg wavelength shift is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Opto-magnetic current sensors were developed in [123] by attaching fibre gratings to magnetostrictive materials such as Terfenol-D, which produces a strain due to the AC magnetic field around the current flowing in a conductor. Simulations on radial and network power systems with opto-magnetic current sensors placed 3 cm away from each phase conductor showed that fault currents can be detected and used for relay operation [124]. An alternative FBG-based current measurement device was built using a piezoelectric stack connected to a Rogowski coil [125].…”
Section: Fault Detection For Power System Protectionmentioning
confidence: 99%
“…Opto-magnetic current sensors were developed in [123] by attaching fibre gratings to magnetostrictive materials such as Terfenol-D, which produces a strain due to the AC magnetic field around the current flowing in a conductor. Simulations on radial and network power systems with opto-magnetic current sensors placed 3 cm away from each phase conductor showed that fault currents can be detected and used for relay operation [124]. An alternative FBG-based current measurement device was built using a piezoelectric stack connected to a Rogowski coil [125].…”
Section: Fault Detection For Power System Protectionmentioning
confidence: 99%
“…The FBG is an optical fiber that serves as a filter for a specific wavelength of light. The principle of the FBGS is to detect the reflected Bragg wavelength shift owing to changes in temperature, strain, or pressure [72], [73]. Fiber Bragg gratings are commonly used optical fiber sensors for measuring temperature and/or mechanical strain.…”
Section: Fiber Optic-based Sensorsmentioning
confidence: 99%
“…FBG sensors have been applied for use in a wide variety of novel uses in medicine, structural health monitoring, environmental monitoring, etc . [ 20 26 ].…”
Section: Sensor Designmentioning
confidence: 99%